Oiliness gradation of hybrid sedimentary shale with low-moderate organic matter content: a case study of the Paleocene Shahejie Formation in Dongpu Depression, Bohai Bay Basin - Zhiming Xiong; Tao Hu; Yuqi Wu; Yunlong Xu; Jiyou Fu; Huiyi Xiao; Yuan Liu; Kuo Zhou; Qinglong Lei; Tianshun Chen; Xiaofei Lin; Mingxing Liu; et al. (International Journal of Coal Science & Technology)
Abstract Shale oil resources are abundant on Earth, of which hybrid sedimentary shale (HSS) oil is an important component, including high and medium–low organic matter content (TOC). Oil content, especially the oiliness gradation, is a key parameter for shale oil evaluation and numerous studies had been conducted. However, most studies concentrated on the HSS with high TOC, making oil content evaluation of the HSS with medium–low TOC challenging. The Paleocene Shahejie Formation (E2s) shale in Dongpu Depression is a typical HSS with low-moderate TOC, showing great shale oil resource potential. Integrated geochemical characterization of 270 core samples were conducted and results show that, the E2s shale has fair-good hydrocarbon generation potential, with TOC ranging from 0.06% to 3.6% (Avg. 0.86%) and II1–II2 kerogen type in thermally mature. The hydrocarbon generation potential decreases with kerogen types changing from type I to III, but S 1C and the oil saturation index (OSI) (S 1*100/TOC > 100) increase from type I to II1, and then decrease from type II2 to III, indicating shale with type II2 kerogen have the greatest oil content. This is related to the differences in hydrocarbon expulsion efficiency caused by differential hydrocarbon generation potential and pore-microfractures evolution among shales with different kerogen types. Significant oil micro-migration occurred in E2s shale, with micro-migration quantity (∆Q) ranging from − 846 to 993 mg/g (Avg. − 120 mg/g), and 90% and 10% shale exhibit hydrocarbon intra-micro-migration (∆Q < 0) and extra-micro-migration (∆Q > 0). The shale with type II2 kerogen has the greatest intra-micro-migration. Based on S 1C, TOC and OSI values and their evolution pattern, shale oil resources were classified into enriched, moderately enriched, less efficient and invalid resources, accounting for 11%, 53%, 16% and 21% respectively, with S 1C thresholds of 3.5 and 0.5 mg/g, OSI threshold of 100 mg/g. Compared with previous grading criteria, the gradation criterion established in this study is relatively lower, which is mainly due to the lower TOC and clay mineral content in HSS. Enriched and moderately enriched resources are mainly shales with type II2 kerogen, followed by type II1 kerogen, and the E2s4 U and E2s3 L shale are the most favorable targets for further shale oil exploration. The established oiliness gradation criteria are applicable for the HSS with TOC in other parts of the world.